Ferramenta de apoio à gestão dos recursos hídricos (FAGRH): sistematização de informações para o processo de tomada de decisões em comitês de bacia hidrográfica com base em indicadores de sustentabilidade - Corrêa, Michele de Almeida (Universidade Federal de São Carlos, 2013)
The model of water resource management decentralized by Basins advocates a broad participation in the decision making process , including technical and non-technical members . This research aimed to develop a tool to support this decision making process in Basins Committees (CBHs) , based on sustainability indicators ( SI) . The development of this research was intermediate steps : 1 ) identification and characterization of CBHs , especially regarding potentially problematic conditions, 2 ) to propose a set of IS to promote the monitoring of the conditions identified in the previous step , 3) the systematization Database (BD) of IS calculated based on official sources for all CBHs of the State of Sao Paulo , 4) structuring the Tool to Support Water Resources Management (FAGRH) , systematized into spreadsheets , 5) simulation application and critical analysis of FAGRH and 6) the consolidation of FAGRH. The consolidated tool proposes the selection of a CBH of the State of Sao Paulo and prioritization of potentially problematic conditions that should be covered in the proposals of this CBH . In the next step FAGRH users are advised to define what are the stages of action to be developed to address each of the priority conditions. For each step, users assign the percentage to be executed and describes one or more actions to achieve this percentage . Also in this step , the user is prompted some information about the action to be performed , such as unit cost , the amount to be performed and the correlation between the action and the proposed IS. In sequence the user is instructed to set the stage of development of each action, assigning a goal to be achieved or the financial investment to be made. With this information the user must then detail the development of proposed actions to compose an Action Plan. As final results FAGRH presents a comparison between the calculated values of IS of the BD and considering the improvements obtained with the proposed actions. The FAGRH also allows checking the percentage of budget involvement for the CBH considering FEHIDRO and FEHIDRO / Levy resources and necessary for the accomplishment of the proposed actions investments. It is noteworthy that the tool has been developed with use of spreadsheets organized in the Microsoft Office Excel file, that is a widely used software. It is concluded that the development of FAGRH collaborates with the organization and systematization of information and can be used to guide the decision making process and to implement tools such as Basin Plans and Information Systems , as well as for the preparation of reports situation.
Keywords: Engenharia urbana; Gestão de recursos hídricos; Processo decisório; Sistema de informação; Indicadores de sustentabilidade; Comitê de bacia hidrográfica; Processo de tomada de decisão; Water resources management; Sustainability indicators; Basin Committee; Decision making process; Information systems; ENGENHARIAS